2018
DOI: 10.3390/tropicalmed3020050
|View full text |Cite
|
Sign up to set email alerts
|

The Health Effects of Strongyloidiasis on Pregnant Women and Children: A Systematic Literature Review

Abstract: Strongyloidiasis is a helminth infection that remains under-researched despite its ability to cause significant illness. Women and children may be at particular risk of health consequences from this parasite. This systematic literature review aims to examine research on the long-term health effects that strongyloidiasis has in pregnant women and children. We conducted a structured search using multiple databases to collect all primary studies discussing health effects of strongyloidiasis in the aforementioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…Clinical complications in organs other than the duodenum have also been described [810]. The health effects of strongyloidiasis on pregnant women should also be considered [11]. Autoinfection of the patients may lead to highly problematic, severe hyperinfections which are almost invariably fatal [1218].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical complications in organs other than the duodenum have also been described [810]. The health effects of strongyloidiasis on pregnant women should also be considered [11]. Autoinfection of the patients may lead to highly problematic, severe hyperinfections which are almost invariably fatal [1218].…”
Section: Introductionmentioning
confidence: 99%
“…16 , 17 A recent systematic review found a mean prevalence of 12.3%, with a median of 6% and higher prevalence in rural areas. 18 Regional variation, pregnancy trimester, and diagnostic methods used may explain most of this variability. Also, the Venezuelan study excluded malnourished pregnant women.…”
Section: Prevalence Of Infection In Pregnant Womenmentioning
confidence: 99%
“… 40 However, of five studies that searched for an association between Strongyloides and maternal anemia, only one found helminth infections to be a predictor of maternal anemia, but helminths were considered as a whole and no differential effect of Strongyloides could be found. 18 …”
Section: Obstetric Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different aspects of diagnosis of strongyloidiasis in hyperendemic regions in northern Australia are presented by Robertson et al [2]. Another review paper on strongyloidiasis focuses on the disease during pregnancy [3]. The authors describe the effects of strongyloidiasis, such as low birth weight and anemia, in children and pregnant women.…”
mentioning
confidence: 99%